Strategi Penentuan Kebijakan Peningkatan Kualitas Hidup Civitas Akademika Dalam Penerapan Kampus Hijau di Universitas Muhammadiyah Riau - Bakaruddin, Bakaruddin; Rahayu, Norra Isnasia; Abunawas, Abunawas (Akuntansi & Ekonomika, 2023)
CO2 emissions are a serious problem that has a direct impact on the environment. Therefore, this paper aims to look at the short and longterm effects of the variables economic growth (GDP), number of industries (JI), foreign investment (FDI) and poverty (KM) on CO2 emissions in Indonesia. Questionnaires were given to 100 academic community respondents, consisting of; lecturers, staff and students at Muhammadiyah University of Riau. This research uses Error Correction Model (ECM) method analysis for the period 1995 to 2019. Empirical results show that the GDP, JI and FDI variables have a significant effect on CO2 emissions, while the poverty variable does not have a significant effect on CO2 emissions in both the short and long term. 1995-2019 in Indonesia.